At-risk serum cholesterol profile at both ends of the nutrition spectrum in West African adults? The Benin study - Delisle, H.; Ntandou, G.; Sodjinou, R.; Couillard, C.; Despres, J. (MDPI, 2013)
Low HDL-cholesterol (HDL-C), using as cut-offs 1.03 mmol/L in men and 1.29 mmol/L in women, was observed in more than 25% apparently healthy adults (n = 541) in a cross-sectional study on nutrition transition and cardiometabolic risk factors (CMRF) in Benin, West Africa. Both overweight/obesity (35.3%) and underweight (11.3%) were present, displaying the double burden of malnutrition. We examined in more depth the association of low HDL-C with nutrition and with other CMRF. Metabolic syndrome components were assessed, plus the ratio of total cholesterol (TC)/HDL-C and serum homocysteine. Insulin resistance was based on Homeostasis Model Assessment. We also measured BMI and body composition by bio-impedance. Dietary quality was appraised with two non-consecutive 24 h recalls. Low HDL-C was associated with much higher TC/HDL-C and more abdominal obesity in men and women and with more insulin resistance in women. The rate of low HDL-C was highest (41.9%) among the overweight/obese subjects (BMI ≥ 25), but it also reached 31.1% among the underweight (BMI < 18.5), compared with 17.3% among normal-weight subjects (p < 0.001). Lower dietary micronutrient adequacy, in particular, in vitamins A, B3, B12, zinc and calcium, was associated with low HDL-C when controlling for several confounders. This suggests that at-risk lipoprotein cholesterol may be associated with either underweight or overweight/obesity and with poor micronutrient intake.